God, Religion and Science - Monjur, Mustafa (Journal of the Bangladesh Association of Young Researchers, 2014)
God, Religion and Science Professor Md. Azizur Rahman Laskar. First Published: March 2014. Sylhet: Pandulipi Prokashon, Bangladesh. 399 pp. Price: BDT 700, 30. ISBN: 978-984-8922-61-3 DOI: http://dx.doi.org/10.3329/jbayr.v2i1.20540 Journal of the Bangladesh Association of Young Researchers (JBAYR): Vol.2(1), 2012 & 2013: 38-40